Specific Features of Canadian Aboriginal Tourism Training in British Columbia - Zhorniak, Nataliya (Pedagogical Discourse, 2012)
The article dwells upon the specific features of aboriginal tourism training in British Columbia. The role of aboriginal tourism in Canadian tourism sector is denoted. The notion of Aboriginal people is defined. The main types of barriers for gaining professional training met by aboriginal people are analysed. Four main principles of providing The First Nations with higher education were studied in detail. Special attention was given to the analysis of the British Columbia Diploma program «Aboriginal Tourism».